If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p(q + 3) = 5 Reorder the terms: p(3 + q) = 5 (3 * p + q * p) = 5 (3p + pq) = 5 Solving 3p + pq = 5 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Reorder the terms: -5 + 3p + pq = 5 + -5 Combine like terms: 5 + -5 = 0 -5 + 3p + pq = 0 The solution to this equation could not be determined.
| 5=r(2r+3) | | 4f-5=8-2f | | 4-5=8-2f | | 35x^2-39x-14=0 | | 5x-2x^2=2 | | 5x^2-46+9=0 | | 0.33z+6=9 | | 5y-2=33 | | 6x+5=78765 | | 6x+5=72 | | 4z+5=18 | | (4x-5)2= | | 8v=3v+20 | | x^3-2x^2-5x+10=0 | | 7u-2=9u | | (3x+8)+(3x-2)=180 | | 2-x=11(x-1) | | (697)(10)= | | 17x^2-11x=0 | | 2x^4y^4+x^3y^3-15x^2y^2=0 | | 36x-9=63 | | 6(4y+14)-13(9y)=100 | | x^2+18x+59=0 | | 8.1x+61.68=-11.9x+60.44 | | 6a^4+7a^2-20=0 | | x*x*x*x-30x*x+125=0 | | 7.2x-3.9=3.3 | | a^4+2a^2-24=0 | | 4x*x*x*x=12x*x | | 5(6z-1)-2(z+3)=21(z+1) | | y^4+y^2-42=0 | | -13x+8x= |